Development Of Learning Video Based Problem To Attract High School Students' Learning Interest On The Material Of Green Chemistry Principles : Penelitian - Kurnia; Rayandra Asyhar; Haryanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Video is an audio visual media that displays images and sound. Learning videos present material, information and explain complex concepts to students in a more interesting way. This learning video is channeled using a problem-based approach. This study aims to determine the feasibility of problem-based learning videos according to the validation of material experts and media experts, to find out teacher assessments and student responses to the media developed. This study is a development research using the Lee & Owens model which consists of the stages of analysis, design, development, implementation and evaluation. The development product was validated by material experts and media experts and assessed by chemistry teachers who were then tested in small groups. The data analysis techniques used were qualitative and quantitative data analysis. The results showed that the learning video obtained a percentage of 87.8% with very decent qualifications from two material experts, 87.8% with very decent qualifications from two media experts and 96% with very good qualifications from chemistry teachers. Meanwhile, in the small group trial, the learning video obtained a percentage of 90.5% with very good qualifications. Based on these results, it can be concluded that the problem-based learning video developed is suitable for use as a medium in the chemistry learning process.